1995
DOI: 10.1152/ajplung.1995.269.4.l514
|View full text |Cite
|
Sign up to set email alerts
|

Heparin and PGE2 inhibit DNA synthesis in human airway smooth muscle cells in culture

Abstract: An increase in the bulk of the airway smooth muscle is a characteristic of asthma. Much of the research investigating the mechanisms of this increase in muscle has focused on mediators that are mitogenic for smooth muscle, while relatively few studies have focused on mediators inhibiting mitogenesis. In this study we have examined the effects of two mediators proposed as regulators of smooth muscle proliferation, namely heparin and prostaglandin (PG) E2, on human airway smooth muscle cells in culture stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
1
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 0 publications
0
82
1
1
Order By: Relevance
“…However, it may also activate other pathways, which could inhibit another cytokine. PGE 2 decreases FBS-induced proliferation of ASM and fibroblasts (9,28). Interestingly, we found that the prostaglandins did not have any pro-or antiproliferative effects on quiesced mesenchymal cells, suggesting that the effects on ECM proteins and cytokine were independent of an effect on cell number.…”
Section: L247mentioning
confidence: 61%
“…However, it may also activate other pathways, which could inhibit another cytokine. PGE 2 decreases FBS-induced proliferation of ASM and fibroblasts (9,28). Interestingly, we found that the prostaglandins did not have any pro-or antiproliferative effects on quiesced mesenchymal cells, suggesting that the effects on ECM proteins and cytokine were independent of an effect on cell number.…”
Section: L247mentioning
confidence: 61%
“…Kaneko et al demonstrated that, although PGE 1 inhibited the growth of human dermal keratinocytes, PGI 1 analogs and PGE 1 enhanced the proliferation of dermal fibroblasts [31]. Moreover, it has been demonstrated that PGE 2 had a biphasic effect on airway smooth muscle cells, with 10 Ϫ6 M causing inhibition and 10 Ϫ7 M causing an increase in DNA synthesis [32]. Although PGE production has been shown to be a self-regulated response that serves to limit the unopposed humoral stimulation of myelopoiesis [24], our data clearly demonstrate that PGE 2 could be a growth-regulatory effector molecule downstream of NO.…”
Section: Discussionmentioning
confidence: 99%
“…Human ASM cells were obtained from subjects without and with asthma by methods adapted from those previously described (26,29), in accordance with procedures approved by the Sydney South West Area Health Service Ethics Committee and the Human Ethics Committee of the University of Sydney. A minimum of three different primary cell lines was used for each experiment.…”
Section: Methodsmentioning
confidence: 99%